Interdisciplinary Exploration of the Advantages and Disadvantages of Agile Methodologies - Luis A. CARDENAS (Communications of International Proceedings, 2024)
The research conducted focused on a systematic literature review to interdisciplinarily analyze the advantages and disadvantages of agile methodologies in various domains, such as software development and marketing. A rigorous methodology was used that combined the systematic literature review with the participation of a panel of experts from different industries that implemented agile methodologies in the first half of 2023. The results highlight flexibility to change, constant value delivery, and improved communication and collaboration as key advantages. However, challenges were identified such as difficulty in long-term planning, possible work overload, and a steep learning curve for those familiar with traditional approaches. It was observed that the effectiveness of agile methodologies can vary depending on the domain and organizational structure. In summary, agile methodologies offer significant benefits in dynamic and collaborative environments, but they also pose challenges that require careful adjustments. The interdisciplinary approach provides a solid foundation for informed implementation and continuous improvement, adapting agile practices to the specific needs and contexts of teams and projects. This study provides a broad perspective that enriches the analysis of agile methodologies, contributing to more adaptable and effective management in modern projects.
Keywords: Agile methodologies; Systematic review; Interdisciplinary approach; Value; Adaptation.